2018
DOI: 10.1021/acs.langmuir.8b01539
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Agent Edelfosine Exhibits a High Affinity for Cholesterol and Disorganizes Liquid-Ordered Membrane Structures

Abstract: Edelfosine is an anticancer drug with an asymmetric structure because, being a derivative of glycerol, it possesses two hydrophobic substituents of very different lengths. We showed that edelfosine destabilizes liquid-ordered membranes formed by either 1-palmitoyl-2-oleoyl- sn-glycero-3-phosphocholine, sphingomyelin (SM), and cholesterol (1:1:1 molar ratio) or SM and cholesterol (2:1 molar ratio). This was observed by differential scanning calorimetry in which phase transition arises from either of these membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…As lipid domain modification seems to actively participate to the phenotype of cancerous cells, they could represent interesting targets for anti-cancer treatments. Actually, edelfosine, a synthetic alkyl-lysoPLP with anti-tumor activity, has been shown to destabilize synthetic membranes composed of POPC (palmitoyloleoylphosphatidylcholine)/SM/chol or SM/chol [ 283 ]. It preferentially localizes in rafts in lymphoma cells, where it inhibits the PI3K/Akt proliferation signaling pathway and promotes the recruitment of the death receptor Fas [ 283 , 284 ].…”
Section: Microvesicle Biogenesis and Shedding—role Of Plasma Membrmentioning
confidence: 99%
“…As lipid domain modification seems to actively participate to the phenotype of cancerous cells, they could represent interesting targets for anti-cancer treatments. Actually, edelfosine, a synthetic alkyl-lysoPLP with anti-tumor activity, has been shown to destabilize synthetic membranes composed of POPC (palmitoyloleoylphosphatidylcholine)/SM/chol or SM/chol [ 283 ]. It preferentially localizes in rafts in lymphoma cells, where it inhibits the PI3K/Akt proliferation signaling pathway and promotes the recruitment of the death receptor Fas [ 283 , 284 ].…”
Section: Microvesicle Biogenesis and Shedding—role Of Plasma Membrmentioning
confidence: 99%
“…This suggests that edelfosine put in motion a series of processes that otherwise would remain dormant in the cancer cell, thus offering a new way to promote cell death in tumor cells. Edelfosine accumulated in rafts (96,199,208,211), showed a high affinity for cholesterol (212,213), enhanced membrane thickness (212,213), and induced an increase in membrane fluidity (214,215). Endogenous FasL/CD95L has also been localized in rafts in human natural killer NK92 cell line (which expresses relatively high endogenous amounts of the protein) and in human T cells after activation (217).…”
Section: Death-promoting Raft Platforms As Therapeutic Targets In Canmentioning
confidence: 99%
“…It is interesting to note that the antitumor alkylphospholipid analog edelfosine, which shows a high affinity for cholesterol (212,213,230) and accumulates in lipid rafts (96,154,199,231,232), displays a rather differential mechanism of action to induce apoptosis in hematological and solid tumor cells (98,233). Edelfosine accumulated at the cell surface lipid rafts in different human leukemic cells, leading to raft reorganization, co-clustering of Fas/CD95 and rafts, and apoptosis (96,154,199,200,208).…”
Section: Differential Proneness To Generate Death-promoting Raft Platmentioning
confidence: 99%
“…The Lo phase is enriched in saturated lipids and cholesterol and, therefore, provides a simple physical model to study raftlike domains (9,10). In this context, it was shown that APLs partition into lipid bilayers and directly interact with Lo domains (11). The observed effects vary depending on lipid composition and the investigated APL (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The observed effects vary depending on lipid composition and the investigated APL (e.g. Edelfosine or Miltefosine) and include: disorganization of Lo domains (11), moderate to significant increase of membrane fluidity (12,13) and stabilization of SM/cholesterol domains (14). More specifically, studies on Erucylphosphocholine (which is more similar to EPC3, due to the shared unsaturated acyl chain) indicate that this APL increases the fluidity of both cellular and model membranes (12), while weakening SM-cholesterol interactions (15).…”
Section: Introductionmentioning
confidence: 99%